2023
DOI: 10.1021/acs.orglett.3c01824
|View full text |Cite
|
Sign up to set email alerts
|

Radical Phosphorylation of Aliphatic C–H Bonds via Iron Photocatalysis

Abstract: The synthesis of tertiary phosphines(III) has been a long-standing challenge in synthetic chemistry because of inevitable issues including harsh conditions, sensitive organometallic reagents, and prefunctionalized substrates in traditional synthesis. Herein, we report a strategically novel C(sp 3 )−H bond phosphorylation that enables the assembly of structurally diverse tertiary phosphines(III) from industrial phosphine(III) sources under mild photocatalytic conditions. The merger of ligand-to-metal charge tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…This means that a radical coupling of the dodecanoyl oxygen radical with the radical adduct A of the undecanyl radical and chlorodiphenylphosphine could proceed to form intermediate B in this reaction, followed by an elimination process to deliver the products 30 and 33 (Scheme 2B, b). The biphosphine compound 31 and the phosphination product 32 of cyclohexane were not observed, implying that this reaction should undergo a different pathway compared with the previous report, 12 and that the reactive chlorine radical could not be generated or play a key role in this transformation. 31 P NMR reaction monitoring experiments were also conducted, and it was found that the single sharp peak of triphenylphosphine oxide as an internal standard spreads gradually over spectral bandwidths within three hours (see the ESI †), perhaps due to the effect of the paramagnetic radical species generated significantly in this reaction.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…This means that a radical coupling of the dodecanoyl oxygen radical with the radical adduct A of the undecanyl radical and chlorodiphenylphosphine could proceed to form intermediate B in this reaction, followed by an elimination process to deliver the products 30 and 33 (Scheme 2B, b). The biphosphine compound 31 and the phosphination product 32 of cyclohexane were not observed, implying that this reaction should undergo a different pathway compared with the previous report, 12 and that the reactive chlorine radical could not be generated or play a key role in this transformation. 31 P NMR reaction monitoring experiments were also conducted, and it was found that the single sharp peak of triphenylphosphine oxide as an internal standard spreads gradually over spectral bandwidths within three hours (see the ESI †), perhaps due to the effect of the paramagnetic radical species generated significantly in this reaction.…”
Section: Resultsmentioning
confidence: 57%
“…Moreover, this method is compatible with various chlorophosphines, even including phosphorus trichloride. 12…”
Section: Introductionmentioning
confidence: 99%
“…Photoinduced LMCT of inexpensive 3d metal complexes (Ni, Cu, or Fe) provides an appealing strategy for hydrogen atom transfer (HAT) with broad applications in C–H functionalizations . Photoinduced LMCT of MCl n is known to generate electrophilic chlorine radicals, which can react with alkane substrates to produce reactive alkyl radicals via the HAT process. , For instance, White’s group reported Fe complexes for oxidation of inactivated C–H­(sp 3 ) bonds . Furthermore, the Zuo group reported the use of abundant cerium salts as photocatalysts for the photocatalytic C–H amination, alkylation, and arylation of methane, ethane, and higher alkanes .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the decarboxylative alkenylation, alkynylation, and thiolation have been developed over past years under case-by-case optimal reaction systems. Based on the insight gained from these important contributions and our research interests in iron-mediated LMCT activation, we recently sought to develop a robust iron-catalyzed decarboxylative condition that generates reactive alkyl radicals under mild conditions and enables a range of useful transformations such as the decarboxylative cross-coupling of carboxylic acids with sulfonyl oximes, decarboxylative alkenylation, alkynylation, thiolation, and amidation (Scheme b). This methodology thus grants access to five different bond-forming reactions under slightly adjusted conditions that can be challenging to accomplish using traditional oxidative decarboxylation methods.…”
mentioning
confidence: 99%